2016
DOI: 10.1371/journal.pone.0146427
|View full text |Cite
|
Sign up to set email alerts
|

The Induction of Heme Oxygenase 1 Decreases Painful Diabetic Neuropathy and Enhances the Antinociceptive Effects of Morphine in Diabetic Mice

Abstract: Painful diabetic neuropathy is a common complication of diabetes mellitus which is poorly controlled by conventional analgesics. This study investigates if treatment with an heme oxygenase 1 (HO-1) inducer, cobalt protoporphyrin IX (CoPP), could modulate the allodynia and hyperalgesia induced by diabetes and enhanced the antinociceptive effects of morphine. In a diabetic mice model induced by the injection of streptozotocin (STZ), we evaluated the antiallodynic and antihyperalgesic effects produced by the intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
32
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 42 publications
7
32
0
2
Order By: Relevance
“…Moreover, protein levels of the antioxidant enzyme HO-1 were significantly increased in the sciatic nerve from db/db mice treated with SFN. In agreement with our data, an increased expression of HO-1 in several tissues from type 1 diabetic animals treated with different Nrf2 or HO-1 inducers compounds has been also previously reported [14, 28, 36, 37]. Tacking account the corroborated antinociceptive properties produced by the activation of HO-1 under inflammatory and neuropathic pain conditions [8, 11, 14], our results suggested that the improvement of the mechanical allodynia induced by SFN in db/db treated mice might be also mediated by enhancing the HO-1 expression in the sciatic nerve of these animals.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, protein levels of the antioxidant enzyme HO-1 were significantly increased in the sciatic nerve from db/db mice treated with SFN. In agreement with our data, an increased expression of HO-1 in several tissues from type 1 diabetic animals treated with different Nrf2 or HO-1 inducers compounds has been also previously reported [14, 28, 36, 37]. Tacking account the corroborated antinociceptive properties produced by the activation of HO-1 under inflammatory and neuropathic pain conditions [8, 11, 14], our results suggested that the improvement of the mechanical allodynia induced by SFN in db/db treated mice might be also mediated by enhancing the HO-1 expression in the sciatic nerve of these animals.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous studies on the effects of vein wrapping, we found that bFGF/CS stimulates Hmox1 mRNA and HO‐1 protein expression, while PBS/CS does not. Previous studies have shown that HO‐1 induction results in anti‐nociceptive effects and alleviation of neuropathic pain . Our results suggest that bFGF/CS‐mediated HO‐1 expression may contribute to pain relief.…”
Section: Discussionsupporting
confidence: 58%
“…Several in vitro and in vivo studies have demonstrated that anti‐oxidants relieve neuropathic pain resulting from peripheral nerve injury . For example, heme oxygenase‐1 (HO‐1) is a rate‐limiting enzyme that catalyzes the oxidative degeneration of heme into biliverdin, carbon monoxide, and iron.…”
mentioning
confidence: 99%
“…For example, heme oxygenase‐1 (HO‐1) is a rate‐limiting enzyme that catalyzes the oxidative degeneration of heme into biliverdin, carbon monoxide, and iron. HO‐1 over‐expression or induction is associated with potent anti‐inflammatory and antinociceptive effects, both in vitro and in mice, and also alleviates neuropathic pain induced by sciatic nerve injury . A recent study reported that bFGF induces HO‐1 expression in spinal cord astrocytes in vitro .…”
mentioning
confidence: 99%